2001
DOI: 10.1006/qres.2000.2199
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Isotope, Diatom, and Pollen Evidence for Late Holocene Salinity Change in a Brackish Marsh in the San Francisco Estuary

Abstract: Analysis of diatoms, pollen, and the carbon-isotopic composition of a sediment core from a brackish marsh in the northern part of the San Francisco Estuary has provided a paleosalinity record that covers the past 3000 yr. Changes in marsh composition and diatom frequencies are assumed to represent variations in freshwater inflow to the estuary. Three periods of relatively high salinity (low freshwater inflow) are indicated, 3000 to 2500 cal yr B.P., 1700 to 730 cal yr B.P., and ca. A.D. 1930 to the present. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
81
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 22 publications
(25 reference statements)
3
81
0
2
Order By: Relevance
“…Much of this coastal population is directly or indirectly affected by coastal flood risks, even as such risks might be mitigated by forward-thinking coastal wetland management and preservation [7]. Stratigraphic and paleoecological evidence documents that coastal wetlands have adapted to marine transgressions and regressions throughout the Holocene [8][9][10][11][12][13]. Hence, coastal wetlands appear to be self-sustaining ecosystems despite human, climate, and sea level impacts.…”
Section: Coastal Wetland Occurrence and Valuementioning
confidence: 99%
“…Much of this coastal population is directly or indirectly affected by coastal flood risks, even as such risks might be mitigated by forward-thinking coastal wetland management and preservation [7]. Stratigraphic and paleoecological evidence documents that coastal wetlands have adapted to marine transgressions and regressions throughout the Holocene [8][9][10][11][12][13]. Hence, coastal wetlands appear to be self-sustaining ecosystems despite human, climate, and sea level impacts.…”
Section: Coastal Wetland Occurrence and Valuementioning
confidence: 99%
“…Palaeoecological techniques have been less widely used in estuaries due to their complex and dynamic nature. However, palaeoecological studies are becoming more frequent (e.g., Byrne et al 2001;Clarke et al 2003;Ellegaard et al 2006;Garcia-Rodriguez 2006;Haynes et al 2007;Plater et al 2000;Ryves et al 2004;Saunders et al 2007Saunders et al , 2008Taffs et al 2008;Weckström 2006;Zong et al 2006). Some of these studies have provided direct management information by addressing long term human impacts such as nutrient enrichment (e.g., Ellegaard et al 2006), the impacts of land use change (e.g., Taffs 2008) and changes in salinity (e.g., Garcia-Rodriguez 2006; Ryves et al 2004).…”
Section: Palaeoecological Techniques and Their Value To Estuarine Manmentioning
confidence: 99%
“…Beyond the period of initial decomposition, several investigations have shown that bulk sediment δ 13 C values are incorporated into coastal sedimentary archives in a manner allowing reliable identification of floral zones after more than 3000 years (Byrne et al, 2001;Malamud-Roam and Ingram, 2004;Lamb et al, 2007). These studies suggested that fractionation of bulk sediment δ 13 C is most pronounced during the short period following deposition of dead plant material and that bulk sediment underwent little further change.…”
mentioning
confidence: 99%